THE TRANSNASAL APPROACH TO SELLAR LESIONS. A NEUROSURGICAL EXPERIENCE AND PERSPECTIVE - Bukhari, Syed Sarmad; Kalsoom, Anisa; Junaid, Muhammad; Raza, Maqbool (Pakistan Armed Forces Medical Journal, 2021)
The transnasal approach for pituitary lesions has been adopted increasingly by neurosurgeons for removing sellar lesions. It has made surgery in this region safer with fewer complications in experienced hands. However, the approach requires good knowledge of nasal anatomy and formal training to achieve good results since the territory is unfamiliar to most neurosurgeons. The approach has a somewhat steep learning curve. In our experience of 41 cases, we have presented here. We have discussed the history of this approach, technique and relevant complications and their avoidance.